Hyalinizing Granuloma: An Unusual Case of a Pulmonary Mass. (14th June 2010) - Brandão, Viviane; Marchiori, Edson; Zanetti, Gláucia; Abdalla, Guilherme; Ventura, Nina; Constantino, Carolina Lamas; Pereira, Mariana Leite; Martins, Pedro; Canellas, Rodrigo; Muccillo, Antonio; Varella de Oliveira, Romulo
Abstract : We describe the case of pulmonary hyalinizing granuloma in a 34-year-old asymptomatic man who presented with a pulmonary nodule apparent by chest radiography and computed tomography (CT). He had a history of previous treatment for tuberculosis. His laboratory data were normal. Bronchoscopy and CT-guided percutaneous transthoracic fine needle aspiration cytology were inconclusive. The diagnosis was revealed after the histopathological examination of an open lung biopsy.